Assembly, organization and regulation of cell-surface receptors by lectin–glycan complexes - Elola, Maria Teresa (2015)
Galectins are a family of β-galactoside-binding lectins carrying at least one consensus sequence in the carbohydrate-recognition domain. Properties of glycosylated ligands, such as N- and O-glycan branching, LacNAc (N-acetyl-lactosamine) content and the balance of α2,3- and α2,6-linked sialic acid dramatically influence galectin binding to a preferential set of counter-receptors. The presentation of specific glycans in galectin-binding partners is also critical, as proper orientation and clustering of oligosaccharide ligands on multiple carbohydrate side chains increase the binding avidity of galectins for particular glycosylated receptors. When galectins are released from the cells, they typically concentrate on the cell surface and the local matrix, raising their local concentration. Thus galectins can form their own multimers in the extracellular milieu, which in turn cross-link glycoconjugates on the cell surface generating galectin–glycan complexes that modulate intracellular signalling pathways, thus regulating cellular processes such as apoptosis, proliferation, migration and angiogenesis. Subtle changes in receptor expression, rates of protein synthesis, activities of Golgi enzymes, metabolite concentrations supporting glycan biosynthesis, density of glycans, strength of protein–protein interactions at the plasma membrane and stoichiometry may modify galectin–glycan complexes. Although galectins are key contributors to the formation of these extended glycan complexes leading to promotion of receptor segregation/clustering, and inhibition of receptor internalization by surface retention, when these complexes are disrupted, some galectins, particularly galectin-3 and -4, showed the ability to drive clathrin-independent mechanisms of endocytosis. In the present review, we summarize the data available on the assembly, hierarchical organization and regulation of conspicuous galectin–glycan complexes, and their implications in health and disease.